KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL BANGUN RUANG GABUNGAN - Juliyansah, Rizky; Hakim, Dori Lukman (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to see how students' ability to solve problems related to surface area and volume of combined space builds. The research method used was qualitative descriptive involving 15 grade VIII students at a junior high school in Karawang Regency. The results showed that there was a variation in students' abilities, only a small percentage of students were able to solve the problem well, while most students still had difficulties. Common mistakes encountered are related to calculations and understanding the concept of building space that has not been fully mastered by most students. This information becomes an important basis for improving the quality of geometry learning in schools, focusing on areas that cause difficulties for students.